(untitled) (Revista de Ciências Agroveterinárias, 2002)
With the objective of evaluating the prevalence of Fasciola hepatica in five counties of the extreme south of Santa Catarina, fecal samples were examined from 290 bovines from different breeds, sex and ages, collected in 61 farms distributed in the counties of Turvo, Jacinto Machado, Meleiro, Timbé do Sul and Morro Grande. The examinations were done by the technique of sedimentation and four sieve. The data were tabulated and analyzed for counties and age range. Individual farms, in the five counties, had a range of animals positive for Fasciola hepatica adult forms from zero to 100%, and among the counties, the range was from 9,09% to 48,35%. Considering the farms that were studied, 63,93% had infected animals for Fasciola hepatica.